2012
DOI: 10.4103/1119-3077.104530
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome in newly diagnosed type 2 diabetes mellitus using NCEP-ATP III, the Nnewi experience

Abstract: The study shows that metabolic syndrome is highly prevalent in newly diagnosed type 2 diabetes patients and the most common risk factor is hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 2 publications
3
19
1
Order By: Relevance
“…14 Studies have also shown consistently that the prevalence of MS increases with age 23,27,31,32,43 Some Nigerian studies found a prevalence of between 10%-35.42% among the general populace. 18,20,21 Specifically, Ulasi et al 18 and Similayi et al 21 using IDF and ATP criteria found a prevalence of between 10.0%-23.19% in suburban centres.…”
Section: Prevalence Of Metabolic Syndromementioning
confidence: 97%
See 3 more Smart Citations
“…14 Studies have also shown consistently that the prevalence of MS increases with age 23,27,31,32,43 Some Nigerian studies found a prevalence of between 10%-35.42% among the general populace. 18,20,21 Specifically, Ulasi et al 18 and Similayi et al 21 using IDF and ATP criteria found a prevalence of between 10.0%-23.19% in suburban centres.…”
Section: Prevalence Of Metabolic Syndromementioning
confidence: 97%
“…[15][16][17][18][19] The prevalence was also higher in the urban compared to the rural areas. 17,[18][19][20] Among patients with type 2 diabetes, prevalence of MS ranged between 59.1%-87.1%, [21][22][23][24] while in patients with hypertension, the prevalence ranged between 24.7%-40.74%. [17][18][19][20][21][22][23][24][25] These Nigerian authors used the WHO, IDF, and Adult Treatment Panel (ATP-III) criteria in their studies.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, after reviewing all the definitions from the WHO, EGIR, and NCEP ATP III, [22][23][24] the International Diabetes Federation (IDF) came out with a new worldwide definition for the metabolic syndrome that placed abdominal obesity as central to the pathogenesis of the metabolic syndrome. 21 Although several Nigerian studies have reported on the prevalence of the metabolic syndrome and some of its components, [25][26][27][28][29] none has addressed the central role of abdominal obesity in the prevalence of the metabolic syndrome in this population. Given that several Nigerian studies have identified abdominal obesity in both adults and children in this population, [14][15][16][17][18][19][20] this study is aimed at assessing the prevalence of the components of the metabolic syndrome in type 2 diabetes mellitus (T2DM) patients using the IDF worldwide definition that was based on abdominal obesity.…”
Section: Introductionmentioning
confidence: 98%